Fiscal federalism and financial resources for regional development - co-operative and competitive models : the international experience - an example for Russia? - Bernhard Seidel; Mechthild Schrooten (Deutsches Institut für Wirtschaftsforschung (DIW), 2000)
In Western economies, the concrete design of fiscal federalism is determined by the status the federation grants to regionally comparable economic and social conditions, and to what extent this status is anchored in the constitution. If the political and social acceptance of regional differences is high, the significance of regional equalisation is low and vice versa. In the case of great regional differences fiscal equalisation could be overburdened by the task of reducing fiscal strength. Moreover, if the political and social acceptance is lacking, regional policy interventions of the federal level is appropriate to support the regional economic convergence rather than fiscal equalisation. However, in high-performing economies organized as federations, comparably weak institutions such as those in Russia are largely unknown. In this sense, international experience makes it clear that strong and well-designed institutional arrangements between the different governmental levels are an important precondition for a high-performing fiscal system. In other words, to take advantage of the potential efficiency gains offered by fiscal federalism, the vertical co-ordination of revenue and expenditure responsibilities between the different governmental levels should be clarified. Problems of destruction and enforcement should be eliminated and replaced by harmonization and co-operation.
Keywords: R58; H7; E60; H1; E62; 330; Fiscal federalism; Russia; regional policy; fiscal equalisation; tax policy; Finanzausgleich; Finanzföderalismus; Regionalpolitik; Finanzverfassung; Übergangswirtschaft; Rußland